PENGARUH MEDIA INTERAKTIF WORDWALL TERHADAP KREATIVITAS SISWA MATA PELAJARAN IPAS MATERI KEBERAGAMAN DAN MELESTARIKAN KEBERAGAMAN BUDAYA KELAS IV DI SDN GULBUNG 1 SAMPANG - Haliza, Nur; Susiloningsih, Wahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low creativity of students in the subject of Natural Sciences, especially in the material of Diversity and Preserving Cultural Diversity, in the process of learning activities students often feel bored and unmotivated because the learning is too monotonous. This has an impact on student creativity as evidenced by the low value of student skills. “The purpose of this study was to determine the effect of the use of interactive wordwall media on the creativity of students in the subject of Natural Sciences, material of diversity and preserving cultural diversity, class IV SDN Gulbung 1 Sampang. Wordwall is a digital learning platform that allows teachers to assist in various interactive and interesting learning activities. By using Wordwall, teachers can create various types of educational games that can increase students' interest and motivation to learn, so that learning becomes more effective and enjoyable. This type of research uses the